2018
DOI: 10.1136/bcr-2018-226769
|View full text |Cite
|
Sign up to set email alerts
|

Third-degree burns associated with transcutaneous pacing

Abstract: A 69-year-old severely obese diabetic woman developed nausea, vomiting and diarrhoea which caused multiple metabolic alterations leading to hypotension and bradycardia due to slow atrioventricular junctional rhythm. Transcutaneous pacing (TCP) was initiated and maintained until the underlying heart rate and blood pressure normalised. TCP gel pads were kept in place prophylactically after pacing was terminated. Gel pads remained attached to the anterior thorax and back for a total of 36 hours. During this time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…They suggested that transcutaneous pacing should be performed for a short duration, if possible. So, physicians should not place the gel pads prophylactically [9]. Singleton et al reported a case of third degree burn injury due to transcutaneous pacing in a patient with third-degree heart block.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that transcutaneous pacing should be performed for a short duration, if possible. So, physicians should not place the gel pads prophylactically [9]. Singleton et al reported a case of third degree burn injury due to transcutaneous pacing in a patient with third-degree heart block.…”
Section: Discussionmentioning
confidence: 99%
“…Another case of pacing-induced burns was believed to be explained by severe obesity (body mass index of 58). 10 Malfunction of the external pulse generator can lead to skin burns via electrolysis if a leakage current is continuously applied at the skin electrode patch during cardiac surgery. 11 Inadequate electrolytic gel at the electrode–tissue interface was likely contributory in a case of pacing-induced burns in which the transcutaneous pacing pads were reused in a Malaysian hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Contudo, os autores ressaltam que os fabricantes sugerem que as almofadas devem ser substituídas diariamente. Portanto, evidencia-se que o MPTC pode estar associado às queimaduras graves e deve ser utilizado com duração mais curta possível, cabendo ao enfermeiro avaliar a integridade da pele do paciente [21][22] .…”
Section: /16unclassified